The Representation of Kartini’s Values in the Diasporic Woman in Rosita Sihombing’s Luka di Champs-Élysées - Miranda, Airin (Franconesia, 2025)
Using the novel Luka di Champs-Élysées by Rosita Sihombing as the corpus, this study aims to identify the local cultural values inspired by Kartini that are represented through the negotiation of global and Indonesian values by the main character, Karima. This research employs a qualitative method with a structural approach as proposed by Robert Stanton (2007) and Burhan Nurgiyantoro (2018), along with transnational feminist theory (Mohanty, Yuval-Davis, and Grewal & Kaplan). These frameworks are connected to Kartini’s values as reflected in her letters (Djojonegoro, 2024) and the field interview findings by the Research Group on Gender, Cultural Identity, and Diaspora, Faculty of Humanities, Universitas Indonesia (2025). The findings reveal that Karima represents Indonesian women in the transnational world who continuously negotiate their identity without being uprooted from their cultural origins. In Karima, Kartini’s values manifest as reflective actions grounded in morality, existential courage, and social responsibility. Karima’s spirituality and religiosity enrich the interpretation of Kartini’s values in the modern context, as her religious experience becomes an integral part of her empowerment and self-recovery process. Therefore, Luka di Champs-Élysées presents a reinterpretation of Kartini’s Indonesian values in the global era—embodying courage, faith, empathy, and social responsibility that remain relevant for contemporary Indonesian women living in transnational spaces.